Breakthrough Thinking in Nursing Education: The Baccalaureate Big 5. (July 2016) - Godfrey, Nelda; Martin, David
Abstract : A deliberate emphasis on breakthrough thinking led to a radically new, evidence-based model for baccalaureate generalist nursing education known as the Baccalaureate Big 5. This semistructured brainstorming process then led to wider application in other settings, creating new nursing education and practice opportunities state wide and nationally. How this was accomplished and how it can be duplicated by others is the intent of this publication.